The causes of early neonatal death in Sulaimani Intensive Care Unite at Maternity Teaching Hospital between Jan 2016 - Feb 2017 - Azize, Pary M.; Muhammad, Layla A.; Kareem, Nasren A. (Kurdistan Journal of Applied Research, 2017)
Early neonatal death refers to all deaths of liveborn infants occurring on or before the first seven days of life. There is a shortage of research on the specific causes of early neonatal death. This study has been conducted in order to assess causes of early neonatal death in Sulaimani's Neonatal Intensive Care Unit at Maternity Teaching Hospital. Information was obtained retrospectively from the patients’ medical records, including (Mother and neonate socio-demographic, Maternal, Fetal and labor causes of death). Generally, this study found that in 2016 out of total 18.573 recorded delivery, 168 early neonatal deaths were analyzed from January 2016 to February 2017. However, this number was declined in comparison to the data of 2015, which estimated around 244 early deaths out of 21.142 total births. The mean age of mothers was ranged (28.22 ±7.69), 73.2% of neonate mothers were multi gravid with 67.3% of them delivered through normal vaginal, The majority of early neonate death was happening in the mean expected date delivery of (28.64 ± 2.90) weeks, with mostly weighing 700- 1.10 gm. Regarding the maternal causes, more than a quarter of the mother had Preeclamptic toxemia followed by (25% antepartum hemorrhage, 22.6% diabetes, respectively), In terms of the fetal causes, more than three-quarter of neonate were dead because of prematurity and the majority 85.2% were deceased because of the respiratory distress syndrome. Almost no labor causes. The study also found that there is a significant association between gravidity, mode of delivery and maternal cause in p value < 0.05. However, that relationship was not found to fetal cause. Moreover, there is also no significant relationship between fetal cause and (Age of mother, Expected date delivery and fetal weight) in p-value > 0.05 accept the gender of the neonate. In conclusion, some factors affecting early neonatal death have been identified in this study special care is essential for these children in order to reduce their mortality rates.